1991
DOI: 10.1071/ea9910347
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of eight cereal and legume species to the compaction status of deep, sandy soils

Abstract: The effects of soil compaction and deep ripping on the growth and yield of crop (wheat, barley, oats, triticale, narrow leaf lupins and field peas) and pasture species (barrel medic and subterranean clover) were investigated for deep, sandy soils near Geraldton, Western Australia. In 1984 (an average rainfall season), growth and yields of all species were substantially reduced by soil compaction. Lupins were not included in the experiment. Barley, wheat and pea yields were reduced by around 45%; oat and tritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…However, with the increasing soil compaction associated with mechanised agriculture and the availability of more powerful tractors and better sub-soilers, ripping can become a beneficial soil management practice. Henderson (1991) reported that deep ripping of compacted, sandy soil increased dry matter at flowering of all species tested by about 30%, seed yields of field peas (Pisum ssp.) and lupins (Lupinus spp.)…”
Section: Soil Compaction and Deep Rippingmentioning
confidence: 99%
“…However, with the increasing soil compaction associated with mechanised agriculture and the availability of more powerful tractors and better sub-soilers, ripping can become a beneficial soil management practice. Henderson (1991) reported that deep ripping of compacted, sandy soil increased dry matter at flowering of all species tested by about 30%, seed yields of field peas (Pisum ssp.) and lupins (Lupinus spp.)…”
Section: Soil Compaction and Deep Rippingmentioning
confidence: 99%
“…1 were uniform bulk densities throughout the 0-20 cm profile of 1.2, 1.4, 1.6, or 1.7g cm -3, corresponding to soil strengths of 0.8, 1.1, 1.7, and 2.4 MPa, respectively. This range of soil densities is typical of the range between non-compacted and compacted field soils reported in the literature (Henderson, 1991;Reeves et al, 1984). Two treatments were used in exp.…”
Section: Soil Compaction Treatmentsmentioning
confidence: 99%
“…Soil compaction can significantly reduce yields of many agronomic species, and in addition to its natural occurrence, has become a chronic problem in many areas due to heavy equipment traffic through the fields (Blackweli et al, 1985Brereton et al, 1986Henderson, 1991). Soil strength and resistance to root penetration increase as soils dry, and therefore even in noncompacted soils the plant response to soil strength is important during drought.…”
Section: Introductionmentioning
confidence: 99%
“…However, concern has been expressed that zero tillage crop production could lead to excess soil compaction. Excess compaction may restrict soil aeration and crop root development, restricting water uptake, nutrient availability and overall crop growth (Henderson 1991). Compaction may be evaluated by penetration resistance and bulk density measurements.…”
mentioning
confidence: 99%